Healthy Living for Elders: Tips for Taking Dietary Supplements - Jennifer Hillan (EDIS)
Dietary supplements include vitamins, minerals, herbs, and other substances. If you are taking any of these products, this document provides some guidelines to help you use them safely. This is document FCS 8623-ENG, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: March 2004.